SISTEM PRODUKSI DAN PENGOLAHAN KOPI BERKELANJUTAN: STATE OF THE ART - Rachman Jaya; Yusriana Yusriana; Rizki Ardiansyah (Faculty of Agricultural Technology, University of Jember, 2019)
Last 10 years, more than 50 papers and handbooks have been published on the topic of sustainable production and processing in the coffee commodity. Review process is used by desk study based on several scientific journals which are related to the topic. It was found by scientific publisher webs such as Scopus, Ebsco, Academia.edu, Researchgate, Portal Garuda, DOAJ and Google Scholar. Technically, sustainability was discussed at least 3 aspects, i.e. economic, social and ecology. In global growth, particularly a coffee commodity has been disturbing production which was caused by global warming, fair-trade and social conflict. On the other hand, dynamically there has been increasing of demand (export and local) due to lifestyle. Based on the fact, the realistic solution is needed on these matters. This study has done several articles reviewed and synthesized. The systematic of it’s through content analysis on that article and then clustered by a topic which assessed. The realistic solution complied based on economic, social and ecology aspects in a sustainable production and processing. Finally, we suggest several new techniques and products (downstream) which could be developed to reach the sustainability and processing of the coffee, especially cold-brew for new coffee product.Keywords: coffee, processing, state of the art, sustainable production